Further analysis of the emotional consequences of head and neck cancer as reflected by the Patients' Concerns Inventory. Issue 8 (October 2015) - Kanatas, A.; Humphris, G.; Lowe, D.; Rogers, S.N.
Abstract: Patients with cancer of the head and neck can experience high levels of distress. The emotional burden of the disease must be recognised and important negative emotions assessed so that appropriate interventions can be provided. We obtained data from 1482 head and neck cancer Patients' Concerns Inventories (HNC-PCI) completed by 813 patients between 1 August 2007 and 9 January 2013, and particularly concentrated on the psychological, emotional, and spiritual well-being domain, which comprises 14 items. We also assessed health-related quality of life (HRQoL) using the University of Washington quality of life questionnaire version 4 (UWQoL). A total of 538 patients were male and the mean age of all patients on first completing the PCI was 64 years (range 20-94). Primary tumours were oral (n = 392, 48%), oropharyngeal (n = 196, 24%), laryngeal (n = 142, 17%), other (n = 74, 9%), or unknown (n = 9, 1%). Fifty-one percent of patients (n = 753) chose no items in the emotions category, 16% (n = 236) identified fear of recurrence only, 16% (n = 236) selected items other than fear of recurrence, and 17% (n = 257) selected fear of recurrence and others. Patients who identified fear of recurrence with other issues had significantly worse scores for anxiety, mood, and overall quality of life (QoL). Fear of recurrence is common but patients with multiple emotional concerns need additional support, and further research is required to specify the practical details of the interventions needed at various points during and after treatment.